Determinan Permintaan Asuransi: Studi Kasus Universitas Surabaya - Theresa Defina Djalu; Sugeng Hariadi; Joshi Maharani Wibowo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The insurance industry in Indonesia has experienced significant development, but the level of insurance usage remains relatively low. The decision to purchase insurance is influenced by several factors, including income level, premium prices, knowledge level, and other social factors. UBAYA, a university in Surabaya, East Java, mandates every employee, lecturer, and student to use insurance provided by the institution with various types, such as employment and life insurance. Nevertheless, some of them choose to add additional insurance beyond what is provided by UBAYA. Therefore, the purpose of this research is to identify the factors influencing individual decisions to add or not add insurance policies beyond those provided by UBAYA. The method used in this research is Social Network Analysis (SNA). The research results indicate that premium prices play a crucial role in the decision to utilize insurance based on individual income levels. Other factors influencing the decisions of UBAYA lecturers and employees include information provided by insurance agents regarding asset protection and options for medical services abroad. The purchase of insurance is influenced by economic and social factors, as well as a comprehensive understanding of personal needs in utilizing the benefits provided by insurance policies. Keywords: Insurance, Premium Price,UBAYA